THE IMPACT OF SYSTEM QUALITY AND INFORMATION QUALITY ON USER SATISFACTION AND USER PERFORMANCE - KAMELIA NURBANI; FAJAR MEIYANTI (Jurnal Akuntansi, Manajemen dan Ekonomi, 2019)
This study aims to analyze the effect of system quality and information quality on user satisfaction and its impact on user performance.The sample selection technique uses purposive sampling is a technique of determining the sample based on specific considerations, which are based on certain characteristics that are considered to have a close relationship with the characteristics of the population that have been previously known in other words the sample units contacted are adjusted to specific criteria applied — based on research objectives. The testing of the hypothesis used is the Structural Equation Modeling (SEM) approach with variance-based structural equation testing, better known as Partial Least Square (PLS) v.3.0.The results of this study indicate that system quality has a significant positive effect on user satisfaction, information quality has a significant positive effect on user satisfaction, and user satisfaction has a significant positive effect on system user performance.